UPAYA MENINGKATKAN MINAT DAN HASIL BELAJAR IPA MENGGUNAKAN MODEL THINK PAIR SHARE SISWA KELAS III SD NEGERI 18 LUBUKLINGGAU - Yurnalis Yurnalis (Jurnal Perspektif Pendidikan, 2021)
This study aims to increase the interest and learning outcomes of third grade science students at SD Negeri 18 Lubuklinggau by using the Think Pair Share learning model. This research is a classroom action research (Action Research) using the Think Pair Share learning model. Based on the results of the study through the Think Pair Share learning model in class III at SD Negeri 18 Lubuklinggau can increase student interest and learning outcomes. Increased interest in learning in the first cycle of the first meeting by 62%, in the second cycle by 70% and in the third cycle 88%. To increase student learning outcomes in the first cycle of the first meeting by 62%, in the second cycle by 70% and in the third cycle 88%. Similar to student interest in learning, student learning outcomes after participating in learning with the Think Pair Share model also increased. This is evidenced by the percentage of students who achieved the KKM score in the first cycle of 20% increased to 60% in the second cycle. Furthermore, it still increased to 80% in the third cycle. This means that the number of students who achieve the KKM score (70) has exceeded the established success criteria of 75%.